(untitled) (Hoboken, N.J., 2007)
Construction Dewatering and Groundwater Control is an indispensable tool for all engineering and construction professionals searching for the most up-to-date coverage of groundwater control for various purposes, the modern ways to identify and analyze site-specific situations, and the modern tools available to control them.
Keywords: Drainage,Soil mechanics,Cơ học đất,Thoát nước